2007
DOI: 10.1016/j.physbeh.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Overweight children habituate slower than non-overweight children to food

Abstract: We have shown that physiological and behavioral responses habituate to food stimuli and recover when novel stimuli are presented. In addition, physiological responses in obese adults habituate slower to repeated food stimuli than those in non-obese individuals, which is related to greater energy intake. The purpose of this study was to test the hypothesis that instrumental responding in overweight children habituates slower to food cues than in their non-overweight peers. Children were provided the opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
(26 reference statements)
5
40
0
Order By: Relevance
“…Finding heightened salivary reactivity in overweight individuals is consistent with previous research demonstrating that overweight adults and children are slower to achieve salivary habituation after repeated exposure to a food cue. 20,21,25 In relation to energy intake, food-cue exposure can have two consequences; it can prime an individual to engage in eating behavior and it can increase the amount of food that is selected and subsequently consumed. 7 We found overweight/lean differences only in the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding heightened salivary reactivity in overweight individuals is consistent with previous research demonstrating that overweight adults and children are slower to achieve salivary habituation after repeated exposure to a food cue. 20,21,25 In relation to energy intake, food-cue exposure can have two consequences; it can prime an individual to engage in eating behavior and it can increase the amount of food that is selected and subsequently consumed. 7 We found overweight/lean differences only in the former.…”
Section: Discussionmentioning
confidence: 99%
“…Also, overweight children are slower to show salivary habituation after repeated exposure to a food cue. 20,21 In adults, obese individuals salivate more in response to a food cue and are slower to develop salivary habituation. [22][23][24][25] However, these findings might otherwise be explained by differences in dietary restraint, [26][27][28][29][30] which is correlated with body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…The point at which the participant begins to work for the alternative reward provides an index of the reinforcing value of the item of interest (36) . Few studies have used this paradigm to compare obese and normal-weight individuals, but one study has found that obese adults work longer for palatable snack foods before switching to liked sedentary activities (37) , and another study has found that overweight children show a slower decline in responding for food over a 20 min period than do normal-weight children (38) . In terms of biological indicators it is interesting that the heightened brain activation in obese compared with normal-weight adults (26)(27)(28) and children (AS Bruce, LM Holsen, R Chambers, L Martin, WM Brooks and CR Savage, unpublished results) is centred on rewardrelated areas including the orbitofrontal cortex and insular cortex.…”
Section: Food-cue Responsiveness and Child Obesitymentioning
confidence: 99%
“…The presentation of a novel food causes dishabituation (2), and stimulus specificity of habituation is observed for the habituating food (3). The rate of habituation to food is related to food consumption, because slower rates of habituation are associated with greater energy intake (4)(5)(6). The rate of habituation within an eating session differs between obese and lean subjects, with obese subjects habituating at a slower rate than leaner subjects (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of habituation to food is related to food consumption, because slower rates of habituation are associated with greater energy intake (4)(5)(6). The rate of habituation within an eating session differs between obese and lean subjects, with obese subjects habituating at a slower rate than leaner subjects (5,7,8). The rate of habituation also predicts weight gain in children, because those who habituate slower show greater gains in BMI z scores than do those who habituate at a faster rate (9).…”
Section: Introductionmentioning
confidence: 99%